2020
DOI: 10.33258/birle.v3i1.850
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Problem Based Learning and Learning Motivation of Mathematical Problem Solving Skills of Class 5 Students at SDN 0407 Mondang

Abstract: This study aims to: 1) find out whether students' mathematical problem solving abilities that are taught with problem based learning are better than students who are taught by direct learning. 2) find out whether the mathematical problem solving ability of students who have high learning motivation is better than students who have low learning motivation. 3) find out whether there is an interaction between learning and student learning motivation towards students' mathematical problem solving abilities. This s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
22
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(29 citation statements)
references
References 0 publications
4
22
0
3
Order By: Relevance
“…Other findings provide strong evidence that the implementation of PBL in enhancing the MPSA and MCUA of primary school students has a high effect size. In their study, (Pohan et al, 2020;Riswari et al, 2018) showed the same results that the implementation of PBL positively affects the MPSA of primary school students. Likewise, (Kaharuddin, 2018) in his study found the same results that the MCUA of primary school students had a positive increase by implementing PBL.…”
Section: B Analysis Of the Study Characteristicsmentioning
confidence: 71%
See 1 more Smart Citation
“…Other findings provide strong evidence that the implementation of PBL in enhancing the MPSA and MCUA of primary school students has a high effect size. In their study, (Pohan et al, 2020;Riswari et al, 2018) showed the same results that the implementation of PBL positively affects the MPSA of primary school students. Likewise, (Kaharuddin, 2018) in his study found the same results that the MCUA of primary school students had a positive increase by implementing PBL.…”
Section: B Analysis Of the Study Characteristicsmentioning
confidence: 71%
“…Researchers collaborating with elementary school mathematics teachers have extensively examined the effect of PBL on mathematical problem-solving abilities (MPSA), mathematical creative thinking skills (MCTA), mathematics communication skills (MCA), mathematical literacy skills (MLA), and mathematical conceptual understanding abilities (MCUA). From several published research reports, some researchers found that PBL has a significant positive effect on enhancing MPSA (Pohan, Asmin & Menanti, 2020;Riswari, Yanto & Sunarso, 2018), MCA (Kodariyati & Astuti, 2016), MCTA (Katminingsih & Widodo, 2015), MLA (Firdaus, Wahyudin & Herman, 2017), and MCUA (Kaharuddin, 2018). However, some researchers also claimed that PBL does not have a significant and even harmed enhancing MPSA (Ali, Hukamdad, Akhter & Khan, 2018), MCA (Rosmala, Isrok'atum & Panjaitan, 2017), MCTA (Indriani, Widyasari & Amril, 2019), and MCUA (Uygun & Tertemiz, 2014).…”
Section: A Introductionmentioning
confidence: 99%
“…According to (Adliani, 2020) students have difficulty in solving problems understanding mathematical concepts. One of the mathematical skills that students must possess and achieve is problem solving (Pohan, 2020). Furthermore, according to Mulyana (2009: 19) mathematical disposition is a change in the tendency of students to view, behave and act when learning mathematics.…”
Section: Review Of Literaturesmentioning
confidence: 99%
“…Additionally, Siron et al (2020) focused on the perception of adopting technology in the learning process, while Cerezo et al (2020) concerned with self-regulated learning for students during the pandemic. The major scholars have demonstrated that problem-based learning, project-based learning, as an attempt to achieve learning goals (Chang et al, 2020;Pohan et al, 2020;Almulla, 2020). However, game-based learning for economics has been overlooked by scholars.…”
Section: Introductionmentioning
confidence: 99%